A method for preparing a cross-linking agent for high temperature fracturing fluid

By synthetic high molecules with multi -linked bistric points as the cross -linking agent ligand to achieve different scale cross -linking, and to improve the stability of the cross -linking structure through a strong partial effect, solve the existing high -temperature cracking cross -linked cross -linking cross -linking The problem that is easy to destroy at high temperature conditions improves the temperature resistance and stability of the fracture fluid.

CN115057964BActive Publication Date: 2025-01-28CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210815611.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-01-28
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

The crosslinking structure of the existing high-temperature fracturing liquid crosslinking agent is easily destroyed under high temperature conditions, resulting in a decrease in viscosity and affecting the performance of the fracturing liquid.

Method used

By synthetic polymer with multi -linked parallel points as the cross -linking agent ligand, the difference between the molecular distribution of the polymer and the molecular weight between the small molecular ligand and the polymer ligand to achieve different scale crosslinters, improve the crosslinker Efficiency, and the stable structure of the cross -linked structure is performed through a group of hydroxyl, carboxyl, sulfate, etc.

Benefits of technology

Improve the temperature resistance and stability of the fracture fluid at high temperature, extend the service life of the crosslinker structure, and meet the requirements of fracture construction above 200 ° C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000008360340000011
    Figure FHA0000008360340000011
  • Figure FHA0000008360340000012
    Figure FHA0000008360340000012
  • Figure GHA0000008360350000061
    Figure GHA0000008360350000061
Patent Text Reader

Abstract

The present invention prepares a polymer containing hydroxyl, carboxyl, sulfonic acid and multi-site coordination structure by copolymerizing functional monomers, nonionic monomers such as acrylamide, and anionic monomers such as 2-acrylamide-2-methylpropanesulfonic acid, as a polymer ligand of zirconium ion, and on this basis, uses inorganic zirconium compounds, nonionic ligands, anionic ligands and polymer ligands as raw materials to prepare a crosslinking agent for fracturing fluid. After testing, the product has a good crosslinking effect on conventional fracturing fluid thickeners, and the formed fracturing fluid system can still maintain good viscosity under high temperature, high salt and shearing, and can be suitable for fracturing operations under harsh conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cross-linking agent for high-temperature fracturing fluid, belonging to the technical field of oilfield chemistry. Background Art

[0002] Oil is the energy with the largest consumption and the widest application field in the world. Its advantages and basic role will remain irreplaceable in the future. With the continuous deepening of oil and gas exploration and development, the proportion of low-permeability, ultra-low-permeability reservoirs and tight oil and gas reservoirs has increased, and low-permeability oil and gas resources account for more than 50% of the total resources. Due to the deep burial depth and low permeability of deep ultra-high temperature reservoirs, the natural production capacity is low or even no after perforation. For those oil and gas wells with very low or even no production in the early stage of production, after fracturing and production increase, they have certain production value and economic benefits. Therefore, fracturing technology has been widely used in low-permeability reservoirs and has become the most effective production increase measure for such reservoirs, achieving good production increase results.

[0003] As one of the most important additives in fracturing fluid, cross-linking agent reacts with thickener through chemical bonds or coordination bonds, so that the macromolecular chains in the thickener are intertwined to form a body network structure, which is further thickened to form a typical viscoelastic jelly, thereby effectively improving the sand carrying capacity and fracture-forming capacity of the fracturing fluid. The cross-linking agent has a great influence on the gelation rate, temperature stability and shear stability of the fracturing system, as well as the permeability of the formation. In the high-temperature resistant fracturing fluid system, the thickener is usually acrylamide polymer, and the cross-linking agent is usually an organic metal ion compound. The metal ions in the cross-linking agent form a coordination effect with the carboxyl group, amide group and other groups in the thickener molecule to achieve cross-linking. By improving the molecular structure of the cross-linking agent, the performance of the fracturing fluid system can be improved.

[0004] Chinese patent document CN104927828 A discloses an organic zirconium crosslinking agent, a fracturing fluid gel and a preparation method thereof, which are prepared from inorganic zirconium salts (5%-10%), polyols (5%-15%), organic ligands (5%-10%), complex crosslinking agents (1%-5%), and high-temperature stabilizers (1%-5%) as raw materials. Among them, the inorganic zirconium salts are zirconium tetrachloride and zirconium oxychloride, the polyols are ethylene glycol, propylene glycol, and mannitol, the organic ligands are acetic acid, lactic acid, dihydroxyethylglycine, sodium gluconate, and triethanolamine, the complex crosslinking agent is N,N-methylenebisacrylamide, and the high-temperature stabilizer is tributyl phosphate, sodium thiosulfate, potassium chloride, and tetraethylenepentamine. The obtained organic zirconium crosslinking agent is used in high-temperature formations, and after shearing for a period of time at 160°C, its viscosity can still meet the construction requirements.

[0005] Chinese patent document CN105199706 A discloses a method for preparing an organic zirconium crosslinking agent, which is prepared from inorganic zirconium salt (5%-25%), organic alcohol (15%-55%), and organic ligand (10%-50%) as raw materials. Among them, the inorganic zirconium salt is zirconium trichloride, zirconium tetrachloride, zirconium oxychloride, zirconium sulfate, zirconium acetate, the organic alcohol is ethylene glycol, glycerol, isopropanol, n-butanol, mannitol, and the organic ligand is glycerol, diethylene glycol, β-diketone, lactic acid, triethanolamine, diethanolamine, and isopropanolamine. The obtained organic zirconium crosslinking agent can be used in the preparation of fracturing fluid. Summary of the invention

[0006] In view of the deficiencies of the prior art, the present invention provides a method for preparing a cross-linking agent for high-temperature fracturing fluid. SUMMARY OF THE INVENTION

[0008] The present invention relates to a method for preparing a cross-linking agent for high-temperature fracturing fluid, and belongs to the technical field of oilfield chemistry. By synthesizing a polymer with multiple complexing sites as a cross-linking agent ligand, the fracturing fluid has good temperature resistance. By utilizing the molecular weight distribution of the polymer and the molecular weight difference between the small molecule ligand and the polymer ligand, cross-linking of different scales is achieved, thereby improving the cross-linking efficiency. Finally, a polymer with hydroxyl, carboxyl, and sulfonic acid groups is prepared, and the strong coordination effect of these groups on zirconium ions under the synergistic effect is utilized to enhance the stability of the cross-linking structure at high temperatures, thereby achieving improved performance of the fracturing fluid.

[0009] Purpose of the Invention

[0010] After acrylamide polymers are formulated into aqueous solutions, they will cross-link with multivalent metal ions to form gels. The commonly used organic zirconium cross-linking agents have improved stability after the introduction of ligands, and the unit cross-linking point strength is increased, thereby improving the stability of the fracturing fluid gel. From the current technical means, cross-linking agents often have the following shortcomings: the cross-linking effect of the cross-linking agent is not good, the amount of thickener and cross-linking agent in the fracturing fluid system is large; the amount of organic ligands is large, and the effective content of high-valent metal ions in the cross-linking agent is small; the cross-linking structure is easily destroyed under high temperature conditions, and the viscosity drops sharply after long-term shearing, affecting the performance of the product. In view of the shortcomings of the prior art, the present invention provides a cross-linking agent for fracturing fluids under high temperature conditions. DETAILED DESCRIPTION OF THE INVENTION

[0012] The technical solution of the present invention is as follows.

[0013] A high temperature fracturing fluid crosslinking agent, the preparation method of which is as follows:

[0014] (1) Preparation of polymer ligands

[0015] Add functional monomer, nonionic monomer, anionic monomer, initiator and deionized water into a three-necked glass bottle equipped with a stirrer, a nitrogen tube and a thermometer, stir until all the raw materials are dissolved, adjust the pH to 6-9, introduce nitrogen for 30 minutes, control the polymerization temperature at 40-80°C, and carry out the polymerization reaction for 1-24 hours. Dry and crush the product to obtain; the molar ratio of the functional monomer, nonionic monomer and anionic monomer is (2-10):(60-90):(5-30), and the mass ratio of the three types of monomers, initiator and deionized water is 1:(0.005-0.05):(1-10);

[0016] (2) Preparation of cross-linking agent

[0017] Add inorganic zirconium compound, nonionic ligand, anionic ligand, polymer ligand and deionized water into a three-necked glass bottle equipped with a stirrer, a condenser and a thermometer, stir until all the raw materials are dissolved, adjust the pH to 3-7.5, control the temperature at 50-90°C, and react for 1-10 hours to obtain; the mass ratio of inorganic zirconium compound, nonionic ligand, anionic ligand, polymer ligand and deionized water is 1:(0.5-5):(0.2-2):(0.1-2):(2-7).

[0018] According to the present invention, preferably, the functional monomer in step (1) is one of functional monomer-A and functional monomer-B.

[0019] Functional monomer-A is

[0020] Functional monomer-B is

[0021] Preferably, the nonionic monomer is one or a mixture of two or more of acrylamide, dimethylaminoethyl methacrylate, vinyl pyrrolidone, vinyl caprolactam, methacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-isopropylacrylamide;

[0022] Preferably, the anionic monomer is one or a mixture of two or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium vinylbenzenesulfonate, sodium vinylsulfonate, and sodium allylsulfonate;

[0023] Preferably, the initiator is one or a mixture of two or more of potassium persulfate, ammonium persulfate, sodium persulfate, azobisisobutylimidazoline hydrochloride, and azobisisobutylamidine hydrochloride;

[0024] Preferably, the molar ratio of the functional monomer, the nonionic monomer, and the anionic monomer is (5-10):(60-80):(20-30);

[0025] Preferably, the mass ratio of the three types of monomers, the initiator, and deionized water is 1:(0.005-0.03):(1-8);

[0026] Preferably, the polymerization temperature is 40-70° C. and the polymerization time is 4-10 h.

[0027] According to the present invention, preferably, the inorganic zirconium compound in step (2) is one of zirconium oxychloride, zirconium trichloride, zirconium tetrachloride and zirconium acetate;

[0028] Preferably, the nonionic ligand is one or a mixture of two or more of triethanolamine, diethanolamine, glycerol, isopropanol, n-butanol, mannitol, methanol, ethanol, and propanol;

[0029] Preferably, the anionic ligand is one or a mixture of two or more of glycolic acid, lactic acid, hydroxypropionic acid, gluconic acid, citric acid, oxalic acid, malonic acid, succinic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid;

[0030] Preferably, the mass ratio of the inorganic zirconium compound, the nonionic ligand, the anionic ligand, the polymer ligand, and the deionized water is 1:(0.5-2):(0.5-1.5):(0.2-1):(3-7);

[0031] Preferably, the cross-linking agent preparation reaction pH is 6-7, the temperature is 60-80° C., and the time is 2-6 hours.

[0032] The excellent effects of the present invention are as follows:

[0033] 1. The raw materials of the present invention are easily available, the process is simple and safe, and the production cost is low.

[0034] 2. Prepare polymers with hydroxyl, carboxyl and sulfonic acid groups, and use the strong coordination effect of these groups on zirconium ions to enhance the stability of the cross-linked structure at high temperatures, thereby improving the temperature resistance of the fracturing fluid.

[0035] 3. The polymer ligand has multiple strong coordination structures. The zirconium ions are loaded on the polymer coordination to form a stable multi-site cross-linking structure, which can reduce the amount of thickener and cross-linking agent in the fracturing fluid system.

[0036] 4. Utilize the molecular weight distribution of polymers and the molecular weight difference between small molecule ligands and polymer ligands to achieve cross-linking of different scales and improve cross-linking efficiency.

[0037] 5. The product of the present invention has simple post-processing and is easy to realize continuous production.

[0038] 6. The product prepared by the present invention has good compatibility with conventional fracturing fluid systems. DETAILED DESCRIPTION

[0039] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0040] The reagents used in the following examples, including thickeners, drainage aids, high-temperature stabilizers, etc., were purchased from Beijing Hongyi Enze Energy Technology Co., Ltd. Other materials, reagents, etc., unless otherwise specified, can be obtained from commercial channels.

[0041] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0042] Embodiment 1:

[0043] (1) Preparation of polymer ligands

[0044] 30 g of functional monomer-A, 130 g of acrylamide, 140 g of 2-acrylamido-2-methylpropanesulfonic acid, 3 g of potassium persulfate, and 500 g of deionized water were added to a three-necked glass bottle equipped with a stirrer, a nitrogen tube, and a thermometer. After stirring until all the raw materials were dissolved, nitrogen was introduced for 30 minutes, the temperature was raised to 55°C, the reaction was carried out for 8 hours, and the product was dried and crushed to obtain a polymer ligand.

[0045] (2) Preparation of cross-linking agent

[0046] Add 20g of zirconium oxychloride, 10g of triethanolamine, 10g of lactic acid, 15g of polymer ligand and 60g of deionized water into a three-necked glass bottle equipped with a stirrer, a condenser and a thermometer. After stirring until all the raw materials are dissolved, add 25% sodium hydroxide solution to adjust the pH to 7, increase the temperature to 80°C, and react for 4h to obtain a cross-linking agent.

[0047] Embodiment 2:

[0048] As described in Example 1, the difference is that the functional monomer in step (1) is functional monomer-B, and the added amount is 30g.

[0049] Embodiment 3:

[0050] As described in Example 1, the difference is that the functional monomer in step (1) is a mixture of functional monomer-A and functional monomer-B, and the added amount is 15g functional monomer-A and 15g functional monomer-B.

[0051] Embodiment 4:

[0052] As described in Example 1, except that in step (1), the nonionic monomers are 80 g acrylamide and 50 g N,N-diethylacrylamide.

[0053] Embodiment 5:

[0054] As described in Example 1, except that in step (1), the nonionic monomers are 50 g acrylamide, 30 g methacrylamide and 30 g N,N-dimethylacrylamide.

[0055] Embodiment 6:

[0056] As described in Example 1, the difference is that in step (1), the anionic monomer is sodium vinylbenzene sulfonate, and the amount added is 100g.

[0057] Embodiment 7:

[0058] As described in Example 1, the difference is that the amount of 2-acrylamido-2-methylpropanesulfonic acid added in step (1) is 170 g.

[0059] Embodiment 8:

[0060] As described in Example 1, the difference is that in step (1), the initiator is azobisisobutylimidazoline hydrochloride, and the added amount is 5g.

[0061] Embodiment 9:

[0062] As described in Example 1, except that in step (1), the polymerization reaction temperature is 70° C. and the reaction time is 5 h.

[0063] Embodiment 10:

[0064] As described in Example 1, except that the amount of triethanolamine added in step (2) is 16 g.

[0065] Embodiment 11:

[0066] As described in Example 1, except that in step (2), the non-ionic ligand is 6 g triethanolamine and 4 g diethanolamine.

[0067] Embodiment 12:

[0068] As described in Example 1, except that in step (2), the anionic ligands are 8 g lactic acid and 5 g citric acid.

[0069] Embodiment 13:

[0070] As described in Example 1, except that the amount of polymer ligand added in step (2) is 10 g.

[0071] Embodiment 14:

[0072] As described in Example 1, the difference is that the amount of polymer ligand added in step (2) is 20 g.

[0073] Embodiment 15:

[0074] As described in Example 1, except that in step (2), the reaction pH is 6, the temperature is 70° C., and the reaction time is 2 h.

[0075] Comparative Example 1:

[0076] Add 20g zirconium oxychloride, 10g triethanolamine, 10g lactic acid and 60g deionized water into a three-necked glass bottle equipped with a stirrer, a condenser and a thermometer, stir until all the raw materials are dissolved, adjust the pH to 7, increase the temperature to 80°C, and react for 4h to obtain the product.

[0077] Comparative Example 2:

[0078] Beijing Hongyi Enze Energy Technology Co., Ltd., GL-3.

[0079] Performance Evaluation

[0080] The rheological properties of the fracturing fluid system prepared by the products of Comparative Examples 1 to 2 and Examples 1 to 15 at high temperature were evaluated. The evaluation was carried out according to the provisions of SY / T 5107-2016 "Method for evaluating the performance of water-based fracturing fluids". -1 The apparent viscosity was measured after shearing for 90 minutes. The test temperatures were 160°C, 180°C and 200°C, respectively. The composition of the fracturing fluid system is shown below. The evaluation results are shown in Table 1.

[0081] Fracturing fluid system formula: 475g deionized water + 24g NaCl + 1g CaCl2 + 3.5g thickener + 10g cross-linker + 12.5g high temperature stabilizer + 15g iron ion stabilizer + 5g demulsifier + 5g drainage agent.

[0082] It can be seen from the data in the table that the fracturing fluid prepared using the cross-linking agent of the present invention has better high temperature stability and can meet the requirements of 200°C fracturing construction.

[0083] Table 1 Performance evaluation results

[0084]

Claims

1. A cross-linking agent for high temperature fracturing fluid, the preparation method of which comprises the following steps: (1) Preparation of polymer ligands Add functional monomer, nonionic monomer, anionic monomer, initiator and deionized water into a three-necked glass bottle equipped with a stirrer, a nitrogen tube and a thermometer, stir until all the raw materials are dissolved, adjust the pH to 6-9, introduce nitrogen for 30 minutes, control the polymerization temperature at 40-80°C, and carry out the polymerization reaction for 1-24 hours. Dry and crush the product to obtain; the molar ratio of the functional monomer, nonionic monomer and anionic monomer is (2-10):(60-90):(5-30), and the mass ratio of the three types of monomers, initiator and deionized water is 1:(0.005-0.05):(1-10); The functional monomer is one of functional monomer-A and functional monomer-B, Functional monomer-A is Functional monomer-B is The nonionic monomer is one or a mixture of two or more of acrylamide, methacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-isopropylacrylamide; The anionic monomer is one or a mixture of two or more of 2-acrylamido-2-methylpropanesulfonic acid, sodium vinylbenzenesulfonate, sodium vinylsulfonate, and sodium allylsulfonate; The initiator is one or a mixture of two or more of potassium persulfate, ammonium persulfate, sodium persulfate, azobisisobutylimidazoline hydrochloride, and azobisisobutylamidine hydrochloride; (2) Preparation of cross-linking agent Add inorganic zirconium compound, nonionic ligand, anionic ligand, the above-mentioned polymer ligand and deionized water into a three-necked glass bottle equipped with a stirrer, a condenser and a thermometer, stir until all the raw materials are dissolved, adjust the pH to 3-7.5, control the temperature at 50-90°C, and react for 1-10 hours to obtain; the mass ratio of inorganic zirconium compound, nonionic ligand, anionic ligand, polymer ligand and deionized water is 1:(0.5-5):(0.2-2):(0.1-2):(2-7); The inorganic zirconium compound is one of zirconium oxychloride, zirconium trichloride, zirconium tetrachloride and zirconium acetate; The nonionic ligand is one or a mixture of two or more of triethanolamine, diethanolamine, glycerol, isopropanol, n-butanol, mannitol, methanol, ethanol, and propanol; The anionic ligand is one of glycolic acid, lactic acid, hydroxypropionic acid, gluconic acid, citric acid, oxalic acid, malonic acid, succinic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid, or a mixture of two or more thereof.

2. The high temperature fracturing fluid crosslinking agent according to claim 1, characterized in that: The molar ratio of the functional monomer, the nonionic monomer and the anionic monomer in step (1) is (5-10):(60-80):(20-30).

3. The high temperature fracturing fluid crosslinking agent according to claim 1, characterized in that: In step (1), the mass ratio of the three types of monomers, the initiator and the deionized water is 1:(0.005-0.03):(1-8).

4. The high temperature fracturing fluid crosslinking agent according to claim 1, characterized in that: In step (1), the polymerization temperature is 40 to 70° C. and the polymerization time is 4 to 10 hours.

5. The high temperature fracturing fluid crosslinking agent according to claim 1, characterized in that: In step (2), the mass ratio of the inorganic zirconium compound, the nonionic ligand, the anionic ligand, the polymer ligand and the deionized water is 1:(0.5-2):(0.5-1.5):(0.2-1):(3-7).

6. The high temperature fracturing fluid crosslinking agent according to claim 1, characterized in that: In step (2), the cross-linking agent preparation reaction pH is 6-7, the temperature is 60-80° C., and the time is 2-6 hours.

Citation Information

Patent Citations

  • Organic zirconium crosslinking agent applicable to polymer fracturing fluid system and preparation method of organic zirconium crosslinking agent

    CN105199706A

  • High temperature resistant organic zirconium crosslinking agent and preparation method thereof, and fracturing fluid gel and preparation method thereof

    CN104927828A

  • Crosslinking agent for sea water-based fracturing fluid as well as preparation method and application of crosslinking agent

    CN106433601A